Implementation of Two Tier Architecture in the Design and Development of Bumdes Administrative Data at the Kelindang Village Office, Bengkulu Tengah - Apriliani, Mentari; Kanedi, Indra; Prasetyo R, Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
The Kelindang Bengkulu Tengah Village Office is one of the villages located in Merigi Kelindang District, Central Bengkulu Regency. So far, the data management process for Village-Owned Enterprises (BUMDes) has used office application packages, namely Microsoft Word and Microsoft Excel. However, not all administrative data processing processes use office application packages, one of which is the 3kg LPG base distribution administration. The Bumdes administration data application at the Kelindang Bengkulu Tengah Village Office is used to make it easier for the village office to process BUMDES administration data, especially regarding the supply and distribution of 3kg LPG Gas to residents within the scope of the Village of Kelindang Bengkulu Tengah. In the data processing process, a network-based two-tier architecture with a WLAN connection has been implemented, to simplify and speed up data input, because many laptops connected to the WLAN can access it. The devices used are 3 units of laptops, namely 1 laptop for the server and 2 laptops for the client. The Bumdes administrative data application at the Kelindang Village Office in Bengkulu Tengah was made using the Visual Basic .Net programming language and SQL Server 2008r2 Database. Based on the tests that have been carried out, the functionality of the Bumdes administrative data application at the Kelindang Village Office in Central Bengkulu is running well and as expected